Long-term exposure to ambient air pollutant and acute exacerbations of chronic obstructive pulmonary disease: a retrospective cohort study in Xinjiang, China - Lian, Zhichuang; Cui, Mengxuan; Liu, Chao; Chen, Ying; Zhang, Ling; Wang, Bei; Yakufu, Nurula; Xu, Jiming; Li, Linfeng; Wei, Xuemei; Kelimu, Julaiti (Frontiers in Public Health, 2025)
IntroductionWhile short-term ambient air pollution is implicated in chronic obstructive pulmonary disease (COPD) exacerbations, evidence for chronic exposure remains limited, particularly in vulnerable subgroups. This study evaluates longitudinal associations between major air pollutants and acute exacerbations (AEs), while identifying high-risk demographic and clinical subgroups.MethodsWe analyzed 660 COPD patients from People’s Hospital of Xinjiang (2020–2023). Annual average concentrations of PM2.5, PM10, O3, NO2, SO2, and CO were geocoded to residential addresses. Single-pollutant logistic regression models adjusted for 12 clinical/sociodemographic confounders assessed AE risks, with robustness verified by two-pollutant sensitivity analyzes. Stratified analyzes examined effect modification across 10 key parameters including disease severity, smoking status, comorbidities, and sociodemographic characteristics.ResultsLong-term ozone exposure demonstrated significant AE risk elevation (OR = 1.007, p = 0.046). This association was confirmed to be robust in two-pollutant models. Stratified analyzes revealed amplified effects in males (OR = 1.009, p = 0.046), those aged over 65 years (OR = 1.012, p = 0.014), Han ethnicity (OR = 1.019, p = 0.003), those with prior-year AEs (OR = 1.008, p = 0.048), and non-asthmatics (OR = 1.014, p = 0.009).ConclusionThis study establishes chronic ozone exposure as an emerging environmental determinant of COPD exacerbations, with disproportionate impacts on vulnerable subgroups. Our findings demand urgent integration of ozone mitigation into national respiratory health strategies and precision public health approaches to address environmental health inequities.